2006
DOI: 10.1007/11861898_41
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Event-Related Desynchronization in EEG, ECoG and MEG Signals

Abstract: We present the results from three motor-imagery-based Brain-Computer Interface experiments. Brain signals were recorded from 8 untrained subjects using EEG, 4 using ECoG and 10 using MEG. In all cases, we aim to develop a system that could be used for fast, reliable preliminary screening in the clinical application of a BCI, so we aim to obtain the best possible classification performance in a short time. Accordingly, the burden of adaptation is on the side of the computer rather than the user, so we must adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
0
29
0
2
Order By: Relevance
“…For overfitting, it is reported that small training set has poor generalization [16]. The overfitting effect is worse when there are a larger number of channels related to the number of trials [15]. We have no idea about how the other factors can influence the generalization.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…For overfitting, it is reported that small training set has poor generalization [16]. The overfitting effect is worse when there are a larger number of channels related to the number of trials [15]. We have no idea about how the other factors can influence the generalization.…”
Section: Resultsmentioning
confidence: 95%
“…With the development of CSP algorithm, the issue of generalization has been gradually noticed [15,16]. The generalization of CSP refers to how far the common spatial filter performs on the testing data from the training data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, identifying neural functions by means of cortical maps can ease the establishment of proper links for neural interfaces that can offer disabled patients an alternative solution for their lost sensory and motor functions through the use of brain-computer interface (BCI) technology [6][7][8][9]. Several recording methods such as electroencephalography (EEG), electrocorticography (ECoG), magnetoencephalography (MEG), positron emission tomography (PET), and functional magnetic resonance imaging (fMRI) have proven to be potentially useful in the implementation of BCI [10][11][12][13][14]. However, due to not having considerable temporal resolution and being large systems, MEG, fMRI, and PET are not practical for continuous recording of electrical signals from neurons.…”
Section: Introductionmentioning
confidence: 99%
“…This method measures the activity from a large population of neurons by attaching electrodes to the scalp of a subject. As a consequence, the impedance of the distance between the cortical tissue and the electrodes force the EEG to have a low spatial resolution [10,15]. Another type of recording technology is the Utah Intracortical Electrode Array (UIEA) which has allowed implanting a large number of microelectrodes into a small area of the cortex due to its micromachined structure.…”
Section: Introductionmentioning
confidence: 99%